Glucagon-like peptide-1 receptor agonists in liver transplant recipients with diabetes: changes in glucose control and cardiometabolic risk factors - Valeria Grancini; Irene Cogliati; Gianfranco Alicandro; Gianfranco Alicandro; Andreina Oliverio; Clara Di Benedetto; Alessia Gaglio; Pietro Lampertico; Pietro Lampertico; Veronica Resi; Emanuela Orsi (Frontiers in Endocrinology)
IntroductionData about efficacy and safety of GLP1 receptor agonists in liver-transplanted patients are lacking.MethodsAmong a population of liver-transplanted individuals with diabetes, we evaluated 68 patients before, 6, 12 and 18 months after starting a GLP1RA-based therapy, as add on to metformin or insulin. We assessed glycemic control, body weight and composition (with bio-impedance analysis), liver fibrosis and steatosis (with transient elastography). Amylase, lipase levels and concomitant therapies were recorded at basal and follow up evaluations. Patients had an e-mail contact to report any adverse events.ResultsWe observed a significant decrease in fasting plasma glucose, HbA1c, weight, BMI, waist circumference. We demonstrated a reduction in total and LDL cholesterol. Liver stiffness decreased during the first 6 months. The rate of adverse events was low and the symptoms reported didn’t require any medical measures: 26.9% reported mild nausea, only 3 patients (7.69%) discontinued the drug dose due to gastrointestinal intolerance. No pancreatitis episodes were detected, amylase and lipase levels didn’t increase (despite concomitant calcineurin inhibitors). No adjustments in immunosuppressant therapy were reported. Among the 45 patients requiring insulin when a GLP1RA therapy was added on, 20 (33.2%) and 31 (45.5%) could suspend insulin therapy at, respectively, 6 and 18 months.DiscussionIn conclusion, GLP1RA-based therapy can be considered safe and effective in a short-term follow up in liver-transplanted patients. Further studies are needed to assess the effects of this drugs on long term complications, such as renal impairment, cardiovascular events and all-cause mortality.